LINGUISTIC CHARACTERISTICS IN SHUHRAT MATKARIMOV’S STORY “YILON” - KADIROVA, Mashhura (Journal of Higher Education and Academic Advancement, 2024)
The role of dialecticism in literary language, artistic work and linguopoetics is the main object of study in this article. Dialectisms used in the language of artistic works in Khorezm literary environment were analyzed. The story “Snake” was studied from the point of view of linguistics based on language fragments